1985
DOI: 10.1111/j.1365-2621.1985.tb10555.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Changes in Mango Fruit During Ripening at Different Storage Temperatures

Abstract: Chemical changes in Haden, Irwin, Kent, and Keitt mangos stored at 1628°C and 85-90% RH were followed to determine the optimum storage and ripening conditions. Weight loss was slightly higher at 25" and 28°C than at 16-22°C. Breakdown in acidity during ripening was slower at 16°C. Vitamin C showed two basic trends; a general decrease as in Haden, Irwin, and Keitt or a steady increase as in Kent. Total and B-carotenoids were significantly higher at 22-28°C than at 1620°C. No significant differences were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
7

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 10 publications
3
35
0
7
Order By: Relevance
“…Similarly, a decrease in titratable acidity of mango fruits during ripening has been reported [15]. Titratable acidity gives a measure of the amount of acid present in a fruit [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a decrease in titratable acidity of mango fruits during ripening has been reported [15]. Titratable acidity gives a measure of the amount of acid present in a fruit [19].…”
Section: Discussionmentioning
confidence: 99%
“…Significant increase in sucrose content of mango has been observed during ripening and this has been attributed to an increase in total soluble solids during ripening. This is due to transformation of starch into soluble sugars as the carbohydrates in the fruit are broken down under the action of phosphorylase enzyme during ripening into simple sugars [15,16]. On the other hand, hydrolysis of starch in the ripening mango fruit has been associated with amylase activity [17].…”
Section: Discussionmentioning
confidence: 99%
“…In 'Irwin', starch is almost undetectable after ripening whereas sucrose increases significantly and fructose slightly (Ito et al, 1997). Vazquez-Salinas and Lakshminarayana (1985) also observed a gradual reduction in glucose and fructose and a continuous increase in sucrose during ripening in 'Haden', 'Irwin', 'Kent', and 'Keitt'. In the mango cultivation system employed in Miyazaki, Japan, mango growers harvest fruits when they naturally drop into the net.…”
Section: Effect Of the Male Parent On Fruit Characteristicsmentioning
confidence: 81%
“…On the other hand, as a result of starch hydrolysis from increased amylase activity during ripening [16] [19], while Selvaraj et al [20] reported glucose as a predominant. Conflicting reports on the relative concentrations of individual sugar, which are presented in mango at different stages of ripening, were attributed to varying cultivars and storage conditions [18].…”
Section: Related Workmentioning
confidence: 99%
“…Conflicting reports on the relative concentrations of individual sugar, which are presented in mango at different stages of ripening, were attributed to varying cultivars and storage conditions [18]. Acid levels are expressed frequently in term of pH and titratable acidity (TA), while sugar concentrations are reported as total soluble solid content (TSS) [19][21] [22]. A few investigators, however, have attempted to understand how concentration varying of these components affects flavor perception of the fruit.…”
Section: Related Workmentioning
confidence: 99%